The profile of leisure time sports people and their reason for doing sport in Spanish sports facilities - Moises Grimaldi Puyana; Pablo Gálvez-Ruiz; Manel Valcarce-Torrente; Ainara Bernal-García (European Journal of Government and Economics (EJGE), 2020)
In Spanish sports habits, there exists a clear increase of the institutionalised sports practice and a distinct trend of leisure and recreational sport. This motivates the current work as it is necessary to go deeply into the knowledge of this practice. The aims proposed are twofold. On the one hand, to perform an analysis of the profile and the characteristics of the behaviour of the users of sports centres and leisure and recreational sportspeople. And, on the other hand, to study the motives of leisure/recreational sports practice. A descriptive quantitative methodology has been followed in this research. The description of the profile of users emerges from the data analysed as well as that they practise sport for exotelic reasons. The results obtained can serve managers to orientate their strategies destined to satisfy the needs of these users.
Keywords: Z0; 330; leisure sport; motives for practice; profile; recreation